PENGARUH KUALITAS LAYANAN DAN KEMUDAHAN MOBILE BANKING TERHADAP KEPUASAN NASABAH PT. BANK SYARIAH INDONESIA.TBK REGIONAL OFFICE X MAKASSAR - M. Fahrul Husni; Ramlah Ramlah; Budhi Krisnanto; Muhammad Rizal; Mirna Mirna (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2023)
Utilizing the use of technology to provide better services to its customers, the bank launched an information technology-based banking transaction service media, namely Mobile Banking (m-banking). As of December 31, 2021, the number of customers using BSI services is 199,499 BSI Mobile Noa Users, from this data, it can be seen that the Mobile Banking services provided by banks are enough to change the lifestyles of people who previously had to queue at the bank, now only with applications. Technological developments that make transactions easier make customers more interested in the Mobile Banking services provided. This research aims to determine the influence of service quality and ease of Mobile Banking on customer satisfaction of PT. Bank Syariah Indonesia Tbk. Regional Office X Makassar. The data analysis methods used are instrument tests, multiple liner analysis, hypothesis tests, and R2 coefficient determination tests. With a total of 100 samples. By the method of taking accidental sampling samples. The results of this test conclude: 1) Service quality has a positive and significant effect on customer satisfaction at PT. Bank Syariah Indonesia Tbk. Regional Office X Makassar. 2) The ease of Mobile Banking has a positive and significant effect on customer satisfaction at PT. Bank Syariah Indonesia Tbk. Regional Office X Makassar. 3) The quality of service and ease of Mobile Banking have a positive and significant effect on Customer Satisfaction at PT. Bank Syariah Indonesia Tbk. Regional Office X Makassar